The agricultural production branch structure formation in the Forest-Steppe - Nechyporenko, Olexandr; Ponomarenko, Oleh; Gryshchenko, Olena (Herald of Economics, 2025)
Introduction. Taking into consideration the existing natural and climatic conditions, the Forest-Steppe zone has significant potential for increasing an agricultural production. At the same time, the existing imbalance between zone`s crop and livestock branches is one of the factors that restrains the Forest-Steppe agricultural sector development and limits its added value growth. Because of that, the issue of detecting deepening branch disproportion internal factors and measuring their impact on changes in the volume of gross agricultural crop and livestock production in the Forest-Steppe zone becomes actual. Study objective means to analyse the current state and detect internal factors that impacted agricultural production branch structure formation in the Forest-Steppe zone in the course of 2019 to 2023.Research methods. General scientific research methods (analysis and synthesis, induction and deduction, historicism), methods of economic analysis (comparative analysis and method of coefficients) and statistical methods (regression analysis and time series) were used.Summary. The article is devoted to internal factors detection that underlie branch disproportion deepening and measuring their impact on changes in the volume of gross agricultural crop and livestock production in the Forest-Steppe zone of Ukraine. To achieve this goal, the formed agricultural production branch structure in the Forest-Steppe zone, its crop and livestock product structure were analyzed and products that experienced the largest average annual increase/decrease in production were identified. Also, the dynamics of sown areas and crop yields, livestock and poultry population and their productivity were studied and analytical calculations were performed to measure factors` influence on changes in the volume of gross agricultural production.Research results. As a result of the study, the main internal factors underlying branch disproportion deepening were detected and their impact on changes in the volume of gross agricultural production in the Forest-Steppe zone of Ukraine was measured.Future prospects. Upon a practical point of view, an analytical basis has been created for making future effective managerial decisions at the macro and regional levels to correct the situation and provide agricultural production in the Forest-Steppe zone of Ukraine with positive developing dynamics.